2023
DOI: 10.3389/fmicb.2022.1100232
|View full text |Cite
|
Sign up to set email alerts
|

Synergic mitigation of saline-alkaline stress in wheat plant by silicon and Enterobacter sp. FN0603

Abstract: Although microorganisms and silicon are well documented as factors that mitigate salt stress, their effect mitigating saline-alkaline stress in plants remains unknown. In this study, wheat plant seeds were treated with silicon, Enterobacter sp. FN0603 alone and in combination of both. Wheat seeds were soaked in silicon and bacterial solutions and sown in pots containing artificial saline-alkaline soils to compare the effects among all treatments. The results showed that the treatments with silicon and FN0603 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that silicon reduces the absorption of sodium ions and increases the ability of SOD, POD, and CAT to remove H 2 O 2 from chloroplasts [45]. The application of silicon fertilizer changed the morphology of plants, increased nutrient content and enzyme activity in rhizosphere soil, and increased the activities of several important antioxidant enzymes (such as SOD) and small molecules (such as proline) [13]. The salt (100 mM NaCl) and silicon (150 mg•L −1 ) treatments increased the activities of SOD, POD, CAT, GR, and APX [46].…”
Section: Effect Of Silicon On Crop Growth Indices and The Antioxidant...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that silicon reduces the absorption of sodium ions and increases the ability of SOD, POD, and CAT to remove H 2 O 2 from chloroplasts [45]. The application of silicon fertilizer changed the morphology of plants, increased nutrient content and enzyme activity in rhizosphere soil, and increased the activities of several important antioxidant enzymes (such as SOD) and small molecules (such as proline) [13]. The salt (100 mM NaCl) and silicon (150 mg•L −1 ) treatments increased the activities of SOD, POD, CAT, GR, and APX [46].…”
Section: Effect Of Silicon On Crop Growth Indices and The Antioxidant...mentioning
confidence: 99%
“…Studies have confirmed that silicon fertilizer is beneficial for plant growth and development and can enhance plant biomass and yield. For example, silicon fertilizer can improve photosynthesis [9,10], increase crop yield by enhancing gas exchange properties and the chlorophyll content in leaves to reduce oxidative damage [11,12], improve root colonization [13], and promote the growth and symbiosis of beneficial microorganisms [14]. Moreover, silicon fertilizer can reduce the harm of insects and pathogens [15]; improve the nutrient utilization efficiency of P, Ca, K, etc.…”
Section: Introductionmentioning
confidence: 99%